2018
DOI: 10.1111/ijd.14254
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic skin donors from a tissue bank in Southern Brazil: clinical and epidemiological profiles and microbial colonization of skin

Abstract: Background An allogeneic human skin graft is a temporary biologic dressing used in extensive burns that can be a providential treatment for affected patients. Skin quality depends directly on its microbial decontamination after processing in a tissue bank. Our objective was to describe the skin donor profiles in relation to the analysis of the microbial colonization of the donated skin.Methods This clinical study includes epidemiological and microbiological data on skin donors from 2012 to 2014. The donor info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Additionally, it was observed that Gram-negative bacteria were especially associated with males with over 7 days stay in an intensive care unit ICU. 40 Analyzing the results obtained in literature 29,[38][39][40] and obtained in this study, a specific preferred deceased donor profile can be proposed. It may be suggested that in the view of microbiological safety, the skin donation should be more preferably executed in the area of operating room than in a forensic facility, and the donor should not stay in an ICU for more than 7 days.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Additionally, it was observed that Gram-negative bacteria were especially associated with males with over 7 days stay in an intensive care unit ICU. 40 Analyzing the results obtained in literature 29,[38][39][40] and obtained in this study, a specific preferred deceased donor profile can be proposed. It may be suggested that in the view of microbiological safety, the skin donation should be more preferably executed in the area of operating room than in a forensic facility, and the donor should not stay in an ICU for more than 7 days.…”
Section: Discussionmentioning
confidence: 70%
“…The results obtained by our team previously 30 also indicated that the donation in operating room conditions was significantly microbiologically cleaner than those prepared in an autopsy room. 30 What is more, the results obtained by Preto et al 40 revealed a significant relationship between the specific hospital in which the tissue collection took place and the number and strain of the isolated microorganisms. Additionally, it was observed that Gram-negative bacteria were especially associated with males with over 7 days stay in an intensive care unit ICU.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…26 As published elsewhere by a tissue bank in Southern Brazil, there is a significant association of a lower average donor age and the presence of microbial colonization of harvested skin allografts. 34 Furthermore, they observed that Gram-negative bacteria were associated with male gender, source hospital and an over 7-day stay in an intensive care unit prior to skin procurement. 34 Besides the microbial burden, the viability of the skin grafts is a crucial issue as well.…”
Section: Introductionmentioning
confidence: 99%
“…34 Furthermore, they observed that Gram-negative bacteria were associated with male gender, source hospital and an over 7-day stay in an intensive care unit prior to skin procurement. 34 Besides the microbial burden, the viability of the skin grafts is a crucial issue as well. The skin bank of Verona (Verona, Italy) observed a mean percentage viability of 45.1 ± 20.1% in cryopreserved allogeneic skin grafts, which is similar to results obtained in other skin tissue banks.…”
Section: Introductionmentioning
confidence: 99%